SOCIAL DIALOGUE AND PARTNERSHIP IN VOCATIONAL EDUCATION AND TRAINING - Zoran Velkovski; Elena Rizova (International Journal of Cognitive Research in Science, Engineering and Education, 2015)
Vocational education and training systems in the Republic of Macedonia have been put under strong pressure for modernisation in the last decades. In addition to economic and political globalisation, technological innovations brought rapid changes in the type of jobs and the content of labour in the national economies, which lead to change of the demand for qualifications and new skills on an on-going basis; the open market and migration expanded opportunities for work within and between countries, and the complexity of the demand for new skills on the labour market have dramatically begun affecting and shaping the structure, organisation and content of vocational education and training. This report is based on the experiences from the collaborative approach applied in the development of the Strategy for Vocational Education and Training in a Lifelong Learning Context for the Republic of Macedonia, implemented through a process of consultation with a broad stakeholder basis. It addresses the participants in the process, the steps undertaken to ensure involvement of stakeholders and ultimately ownership over the process (or its components), the obstacles encountered and steps undertaken to address them, the problems, their causes and proposals for preventing and/or eliminating them, as well as the lessons learned and recommendations for further development of the social dialogue and partnership.